Homoplantaginin inhibits the progression of ulcerative colitis in mice by regulating the MMP9-RLN2 signaling axis - Tao, Yu; Shao, Rongrong; Cui, Mengting; Wang, Haojie; Xiang, Manman; Ge, Sitang; Deng, Min; Li, Xian; Liu, Fang; Fan, Fangtian (Frontiers in Medicine, 2025)
IntroductionUlcerative colitis (UC) is a chronic inflammatory bowel disease characterized by colonic mucosal inflammation and ulceration. This study investigates the therapeutic effects of homoplantaginin (Homo), a flavonoid derived from Salvia plebeia R. Brown, on dextran sulfate sodium (DSS)-induced colitis in mice, as well as its underlying mechanisms of action.MethodsIn this study, a mouse colitis model was established using DSS to assess the remission effect of Homo on colitis mice. Quantitative reverse transcription PCR (qRT-PCR) was employed to investigate the impact of Homo on intestinal mucosal barrier and pro-inflammatory cytokines in mice. The possible target genes of Homo were analyzed and screened using bioinformatics and molecular docking approaches. Microscale Thermophoresis (MST) technique was employed to examine the binding interaction between Homo and its target gene, matrix metalloproteinase 9 (MMP9). Finally, the combination of Homo and MMP9 inhibitors was utilized to verify whether Homo alleviates DSS-mediated colitis in mice through modulation of MMP9.ResultsHomo (50 mg/kg) significantly alleviated colitis symptoms, lowered myeloperoxidase (MPO) activity, and improved histopathological outcomes. qRT-PCR analysis revealed that Homo inhibited the expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6 and IFN-γ) and related molecules, highlighting its anti-inflammatory properties. Additionally, Homo strengthened the intestinal mucosal barrier by regulating barrier protein expression. Bioinformatics analysis identified that MMP9 as a potential target of Homo, while molecular docking and MST analysis revealed a dose-dependent inhibition of MMP9. Moreover, the MMP9/Relaxin 2 (RLN2) signaling pathway was implicated in Homo’s effects, as evidenced by the upregulation of RLN2 mRNA upregulation and its interaction with MMP9. The combination of the MMP9 inhibitor IN-1 with Homo demonstrated no synergistic effect, it confirmed the role of the MMP9-RLN2 axis in colitis modulation.ConclusionHomo demonstrates significant potential in alleviating colitis through targeting the MMP9-RLN2 signaling pathway, warranting further clinical investigation in UC treatment.